Modulating Beta-Cardiac Myosin Function at the Molecular and Tissue Levels - Tang, Wanjian; Blair, Cheavar A.; Walton, Shane D.; Málnási-Csizmadia, András; Campbell, Kenneth S.; Yengo, Christopher M. (Frontiers in Physiology, 2017)
Inherited cardiomyopathies are a common form of heart disease that are caused by mutations in sarcomeric proteins with beta cardiac myosin (MYH7) being one of the most frequently affected genes. Since the discovery of the first cardiomyopathy associated mutation in beta-cardiac myosin, a major goal has been to correlate the in vitro myosin motor properties with the contractile performance of cardiac muscle. There has been substantial progress in developing assays to measure the force and velocity properties of purified cardiac muscle myosin but it is still challenging to correlate results from molecular and tissue-level experiments. Mutations that cause hypertrophic cardiomyopathy are more common than mutations that lead to dilated cardiomyopathy and are also often associated with increased isometric force and hyper-contractility. Therefore, the development of drugs designed to decrease isometric force by reducing the duty ratio (the proportion of time myosin spends bound to actin during its ATPase cycle) has been proposed for the treatment of hypertrophic cardiomyopathy. Para-Nitroblebbistatin is a small molecule drug proposed to decrease the duty ratio of class II myosins. We examined the impact of this drug on human beta cardiac myosin using purified myosin motor assays and studies of permeabilized muscle fiber mechanics. We find that with purified human beta-cardiac myosin para-Nitroblebbistatin slows actin-activated ATPase and in vitro motility without altering the ADP release rate constant. In permeabilized human myocardium, para-Nitroblebbistatin reduces isometric force, power, and calcium sensitivity while not changing shortening velocity or the rate of force development (ktr). Therefore, designing a drug that reduces the myosin duty ratio by inhibiting strong attachment to actin while not changing detachment can cause a reduction in force without changing shortening velocity or relaxation.